Odour reduction strategies for biosolids produced from a Western Australian wastewater treatment plant: Results from Phase I laboratory trials - Gruchlik, Yolanta; Heitz, Anna; Joll, Cynthia; Driessen, Hanna; Fouche, L.; Penney, N.; Charrois, Jeffrey (I W A Publishing, 2013)
This study investigated sources of odours from biosolids produced from a Western Australian wastewater treatment plant and examined possible strategies for odour reduction, specifically chemical additions and reduction of centrifuge speed on a laboratory scale. To identify the odorous compounds and assess the effectiveness of the odour reduction measures trialled in this study, headspace solid-phase microextraction gas chromatography-mass spectrometry (HS SPME-GC-MS) methods were developed. The target odour compounds included volatile sulphur compounds (e.g. dimethyl sulphide, dimethyl disulphide and dimethyl trisulphide) and other volatile organic compounds (e.g. toluene, ethylbenzene, styrene, p-cresol, indole and skatole). In our laboratory trials, aluminium sulphate added to anaerobically digested sludge prior to dewatering offered the best odour reduction strategy amongst the options that were investigated, resulting in approximately 40% reduction in the maximum concentration of the total volatile organic sulphur compounds, relative to control.